Nanny families Practices of care by nannies, au pairs, parents and children in Sweden - Anving, Terese (Bristol University Press, 2019)
Available open access under CC-BY-NC license. Using Sweden as a case study, this book combines theories of family practices, care and childhood studies with the personal perspectives of nannies, au pairs, parents and children to provide new understandings of what constitutes care in nanny families.